STRATEGI PEMBANGUNAN EKONOMI PERSPEKTIF ISLAM DAN RELEVANSINYA TERHADAP PEMBANGUNAN INDONESIA - Mubarok, Muhammad Sultan (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to explain (1) how the concept of economic development in Islamic perspective; (2) how the general principles of economic development in Islam; and (3) how the relevance of the development of Islamic perspective in Indonesian Development. The research methodology uses a qualitative approach with the type of library research, the data collected is then analyzed using inductive analysis. The results of the study found that the focus of Indonesia's development in the last 10 years, seen in the perspective of Islamic development has not been relevant, this is because the focus of the Indonesian government is still building infrastructure not on the aspect of human resources. Borrowing the term from K.H. Abdurrahman Wahid